Karonese Language Shift of Young Generation - Tita . Nurmaliya; Siti Aisyah Ginting; Anna Riana Suryanti Tambunan (LINGUISTIK TERAPAN, 2022)
This study deals with Karonese Language Shift of Young Generation. It employs qualitative research design with a case study. This study aims to describe: the reasons for Karonese shift into Indonesian language. The subjects were 20 young generations of Karonese, 10 young generations of intramarriage family and 10 young generations of intermarriage family. They were chosen from 10 young generations whose parents are Karonese father and mother and 10 young generations whose parents are Karonese father and Non Karonese mother. The ages range of the subjects were between 13-17 years old. The instruments used for this study were questionnaire and interview. The interview was used to obtain the reasons of language shift. The data were analyzed by Miles, Hubberman and Saldana’s data analysis. There are two reasons of Karonese young generations use Indonesian language, the first is status of Indonesian language, there are (20%) of young generations from intramarriage family answer this reason and the rest of (80%) use Indonesian language because of social success. There are (50 %) of Karonese young generations from intermarriage family use Indonesian language because of the status of the language. The rest (50%) of the young generations use Indonesian language because of social success.